Systemic Antimicrobial Therapy for Diabetic Foot Infections: An Overview of Systematic Reviews - Angela Wright; Stephen Wood; Janath De Silva; J. Simon Bell (MDPI AG, 2023)
Diabetic foot infections (DFIs) are a common complication of diabetes; however, there is clinical uncertainty regarding the optimal antimicrobial selection. The aim of this review was to critically evaluate the recent systematic reviews on the efficacy and safety of systemic (parenteral or oral) antimicrobials for DFI. Medline, Embase, CENTRAL, and CINAHL databases and the PROSPERO register were searched from January 2015 to January 2023. Systematic reviews with or without meta-analyses on systemic antimicrobials for DFI, with outcomes of clinical infection resolution or complications, were included. Of the 413 records identified, 6 systematic reviews of 29 individual studies were included. Heterogeneity of individual studies precluded meta-analysis, except for ertapenem versus piperacillin-tazobactam (RR 1.07, 95% CI [0.96-1.19]) and fluoroquinolones versus piperacillin-tazobactam (RR 1.03, 95% CI [0.89-1.20]) in one review. The application of the AMSTAR-2 tool determined two reviews to be of high quality. There was no statistical difference in the clinical resolution of infections for 24 different antimicrobial regimens (penicillins, cephalosporins, carbapenems, fluoroquinolones, vancomycin, metronidazole, clindamycin, linezolid, daptomycin, and tigecycline). However, tigecycline did not meet non-inferiority against ertapenem ± vancomycin (absolute difference −5.5%, 95% CI [−11.0-0.1]) and was associated with a higher incidence of adverse drug events. There is minimal systematic review evidence to suggest one regimen is superior to another for DFI.